Level Of Understanding of TBI Students Towards Plagiarism at Stain Majene - Aulia Fitri Al-Azizah, Dheanda (Eduvelop: Journal of English Education and Development, 2023)
This study aimed to determine the level of understanding of students regarding plagiarism. In this study the author used the Mixed Method method, which was a combination of quantitative and qualitative methods in one study. Mixed Method is a method using a combination of research procedures, where one method is more dominant than the other. Less dominant methods are only positioned as complementary methods as additional data. The more dominant method in this study is quantitative method and as a complementary method is qualitative method. Data obtained through distributing questionnaires to students. In analyzing the data the author uses the average formula and finally uses the category of understanding. From the research conducted to all TBI students of STAIN Majene West Sulawesi, it was found that the level of understanding of TBI students towards plagiarism was less understanding. The limitations in this study are the lack of student interest in filling out the questionnaire that has been distributed by the author so that the data obtained is less than the number of samples..